(untitled) (Acta Scientiarum. Agronomy, 2015)
Soil compaction associated with pastures degradation can decrease animal productivity, forage longevity and compromise environmental sustainability. To confront this serious issue, the loosening potential of forages should be recognized. We evaluated the least limiting water range as indicator of biological loosening potential in relation to cultivation of grasses the genus Brachiaria in crop-livestock integration. We also evaluated the water availability to soybean crop that succeeded these grasses. Our studies were performed in two stages. In the first stage, we divided 32 plots into four randomized blocks in which we cultivated corn combined with following treatments: 1 - Brachiaria brizantha cultivar Marandu; 2 - Xaraes; 3 - Piata; 4 - MG4; 5 - B. decumbens; 6 - B. ruziziensis; 7 - Invasive plants; and 8 - uncovered soil. We evaluated soil, to quantify the biological soil loosening, and also forages. In the second stage, we cultivated soybean and added: 9 - conventional tillage as a control treatment, increasing number of plots to 36. Our results suggest that it is possible to cultivate Brachiaria brizantha or Brachiaria decumbens as management strategy to aid edaphic recovery. Xaraes and Piata grasses provide greater soil loosening while increasing water availability to successive soybean crop.